Barriers and facilitators for smoking cessation in chronic smokers with atherosclerotic cardiovascular disease enrolled in a randomized intervention trial: A qualitative study - Getz, Vilde; Munkhaugen, John; Lie, Hanne C.; Dammen, Toril (Frontiers in Psychology, 2023)
Background and Objectives: Smoking is common in patients with cardiovascular disease. Despite strong recommendations for cessation and the existence of efficacious pharmacological and behavioral interventions, cessation rates remain low. Therefore, in this study, we explore perceived facilitators and barriers to smoking cessation in patients with atherosclerotic cardiovascular disease who have participated in a cessation intervention study. Methods: Participants (N = 10) from the intervention arm of a randomized controlled study with access to free cessation support and pharmacological aids completed a semi-structured, in-depth telephone interview after the six months follow-up between October 2021 and July 2022. Interviews were audio-recorded, transcribed, and analyzed according to principles of thematic analysis. Results: Mean age was 65.7 (range 55 to 79) years, and three out of 10 participants were female. Five had quit smoking, three had relapsed and two were persistent smokers. The themes identified encompassed barriers and facilitators to cessation, both including individual and contextual factors. Barriers included: Upsides of smoking, difficult life situations, addiction to smoking, smoking in social circles, and perceived lack of support and understanding from health professionals. Facilitators included: Intrinsic motivation, concerns about the health condition, financial implications, specific behavioral strategies, positive influence from the social environment, and helpful components of the cessation intervention. Conclusions: Smokers with cardiovascular disease who have attended a cessation intervention study report several facilitators weighted against barriers, interacting with the intention to cease smoking. The most important potentially modifiable factors of significance for cessation identified may be addressed through motivational interviews and focus groups with other smokers.